Carrapatos e riquétsias em javaporcos (Sus scrofa scrofa) em uma fazenda do município de Tupaciguara - Minas Gerais e Análise proteômica da saliva dos carrapatos Amblyomma sculptum e Amblyomma parvum - Sousa, Ana Carolina Prado (2022)
Wild boars or feral pigs are considered by IBAMA as an invasive exotic species through the European wild boar (Sus scrofa), in all its forms (native, domestic, feral and mixed), lineages, breeds and different degrees of crossing with the domestic pig. In Brazilian territory they are classified in "Category I of invasive exotic species" because they alter biotic processes and cause social and economic damage, in addition to acting as hosts for some tick species, including the genus Amblyomma. This genus stands out in animal and public health due to the wide variety of hosts used by tick species and being vectors of pathogens, some zoonotic, such as bacteria of the genus Rickettsia. Therefore, the purpose of this work was to identify the species of ticks present in the environment and parasitizing wild boars on a farm in Minas Gerais state, Southeastern Brazil, in addition to tracking the presence of rickettsiae and the degree of exposure of vertebrate hosts in these arthropods to rickettsiae species of Spotted Fever Group and R. bellii through serology. In total, 3585 ticks were collected, and three species of ticks were identified: Amblyomma sculptum, A. dubitatum and Rhipicephalus sp. The most abundant and collected species in all study sites was A. sculptum. A total of 31 wild boars were captured and 415 ticks were collected, all A. sculptum species. In no sample of A. sculptum and Rhipicephalus sp. collected from the environment or A. sculptum of javaporcos there was amplification of the gltA gene; however, all A. dubitatum ticks showed amplification of the specific sequence of the gltA gene of the R. bellii, and no amplification of the OmpA and OmpB genes. Of the 31 wild boar serum samples, 24 reacted with at least one Rickettsia antigen; 07 individuals showed reaction to a possible homologous antigen (PAH) of three rickettsia species, R. rickettsii (n=3), R. amblyommatis (n=3) and R. rhipicephali (n=1). These results provide subsidies to support public health actions in prevention of vector-borne diseases in areas of overlapping capybaras, wild boars and other wild and domestic animals, since additional studies are needed to establish the capacity of wild boar/javaporcos to become infected by ticks, amplify the bacteria and its role in the transmission/maintenance cycle of Rickettsia spp.Ticks are obligate hematophagous ectoparasites that have the ability to parasitize an extensive set of vertebrate hosts, integrating the second main group of vector agents of medical and veterinary importance. When they feed, the saliva produced has numerous pharmacologically active molecules involved in fixation to the hosts' skin, and in the control of their hemostatic, inflammatory and immune reactions, among other functions. Among the main tick species of medical and veterinary importance in Brazil, Amblyomma sculptum tick stands out, one of the vectors of Brazilian Spotted Fever; Amblyomma parvum, which frequently bites humans, is associated with pathogenic microorganisms such as Coxiella burnetti. The identification and specification of saliva constituent elements help to understand how ticks modulate host defense responses; therefore, a proteomic analysis using liquid chromatography associated with a mass spectrometer (LC-MS/MS) was performed on the saliva of A. sculptum ticks, fed on two different hosts and A. parvum, fed on rabbits, to verify the diversity of ticks. substances found and relate to established databases. In the proteomic profile of A. parvum saliva, 130 proteins belonging to 30 different families were recognized. Of these, 117 belonged to the tick (90%), and only 13 to the vertebrate rabbit host (10%); the largest amount of proteins identified were protease inhibitor family (15.6%), which represents one of the main components of the molecular biology of tick saliva responsible for feeding success. 106 proteins were identified in A. sculptum tick saliva fed on rabbits, most of which correspond to the cyclophilin-type PPIASE family, which may be involved in the initiation of T cell activation; and 347 proteins in A. sculptum saliva fed on naturally infested horses, as the Actin and Phosphoprotein families were the most frequent. Also from A. sculptum, 06 proteins (1.72%) belonged to the horse vertebrate host and only 03 (2.83%) to the rabbit host. Most of the identified host proteins corresponded to proteins related to the immune response. The different approaches used in protein separation, acquisition of mass spectra and data analysis allowed the identification and characterization of a significant number of possible target proteins for vaccine candidates and/or pharmacologically active molecules.